1971
DOI: 10.1111/j.1432-1033.1971.tb01355.x
|View full text |Cite
|
Sign up to set email alerts
|

Isoleucyl‐tRNA Synthetase

Abstract: Fluorescence properties of purified isoleucyl-tRNA synthetase isolated from Escherichia coli B have been studied. No changes in the quantum yield, energy or polarisation of the emission were detected in the presence (either individually or in combinations) of the substrates and cofactors required for activation of L-isoleucine.In 2.5 M urea enzyme activity and intrinsic fluorescence intensity (at 340 nm) each decrease with time, showing similar kinetics and rate constants. The rate of this decay is reduced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

1973
1973
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 21 publications
3
11
0
Order By: Relevance
“…The results are listed in Table 1 together with some related data [17 -201. The value of 4.23 for pKE2(E-AMP) agrees well with the value of 4.3 which was determined earlier [21]. The predominant site of protonation in the &-adenine moiety is N-6 [13,16,22] while in the parent adenine moiety it is N-1 [18].…”
Section: Acidity Constants Of H2(and-amp) H 2 ( a M P ) And H( Ump)supporting
confidence: 86%
“…The results are listed in Table 1 together with some related data [17 -201. The value of 4.23 for pKE2(E-AMP) agrees well with the value of 4.3 which was determined earlier [21]. The predominant site of protonation in the &-adenine moiety is N-6 [13,16,22] while in the parent adenine moiety it is N-1 [18].…”
Section: Acidity Constants Of H2(and-amp) H 2 ( a M P ) And H( Ump)supporting
confidence: 86%
“…However, when incubated in the presence of its ligand, NADH, the enzyme was to a certain extent protected against inactivation. Ligand protection of an enzyme against inactivation has previously been used for determination of the dissociation constant for enzyme -ligand complex [3].…”
Section: Ligand-protecting Methodsmentioning
confidence: 99%
“…The ligand protection method is based on the fact, that a n enzyme to some extent is protected against denaturation, when a ligand is bound to it. Thus, a relationship exists between the dissociaton constant for the ligand -enzyme complex and the denaturation rate of the enzyme [3].…”
mentioning
confidence: 99%
“…O n the one hand, there are methods that do not involve the isolation of complexes; for instance, studies of the effect of substrates on the thermostability of the synthetases (79)(80)(81), on resistance to proteolysis (81), or the action of other denaturing factors (82) or studies of the effect of substrates on the fluorescence of the enzyme (28,38,(83)(84)(85)(86)(87). Fluorescence techniques are used to investigate such characteristics of the enzyme as quantum yield, position and halfwidth of the fluorescence maximum of the aromatic amino acid residues of the enzyme protein (mainly tryptophan) (28,38,83), or the kinetics of the fluorescence quenching in the presence of denaturing agents (85). Both approaches-inactivation studies and fluorescence techniques-have been applied to study the binding of all three substrates.…”
Section: A Detection and Isolationmentioning
confidence: 99%
“…However, studies of the complexes alone cannot prove any reaction route because direct information to this end can be obtained only by kinetic methods. Moreover, it has been demonstrated for a number of synthetases that each substrate alone (in the absence of other substrates) is bound by the enzyme (28,38,85,88). At the same time the evidence obtained by investigation of the complexes does not contradict the results of kinetic studies: it was found by means of gelfiltration techniques that ATP forms complexes with leucyl-tRNA (125), threonyl-tRNA (124), and tryptophanyl-tRNA (1 17,118) synthetases.…”
Section: A Tp-ppi Exchangementioning
confidence: 99%